META-SINTESIS: SELF-ESTEEM DALAM HARD SKILL MATEMATIK SISWA - Cholifah Cholifah; Scolastika Mariani; Arief Agoestanto (Universitas Muhammadiyah Surabaya, 2025)
Challenges in mathematics education are becoming increasingly complex, particularly in achieving a balance between students’ hard skills and soft skills. One crucial aspect of soft skills is self-esteem. This article aims to examine the relationship between self-esteem and students’ mastery of mathematical hard skills through a meta-synthesis approach. Data were collected from articles published between 2020 and 2025, focusing on self-esteem in the context of mathematics proficiency. The search strategy utilized the Publish or Perish software, Google Scholar, and the PRISMA 2020 framework. The analysis results indicate that self-esteem has a positive impact on the mastery of mathematical hard skills by fostering students’ confidence, creativity, and learning independence. This study highlights the importance of incorporating affective aspects—particularly self-esteem—into instructional strategies to optimally support students’ cognitive abilities